Perceptions of thermal comfort and coping mechanisms related to indoor and outdoor temperatures among participants living in rural villages in Limpopo province, South Africa. (December 2022) - Wright, Caradee Y; Wernecke, Bianca; Kapwata, Thandi; Kunene, Zamantimande; Mathee, Angela; Vande Hey, Joshua; Theron, Linda
Global heating is considered one of the greatest threats to human health and well-being. Supporting human resilience to heating threats is imperative, but under-investigated. In response, this article reports a study that drew together results from quantitative data on perceptions of thermal comfort and mechanisms for coping with thermal discomfort among 406 households in a study in Giyani, Limpopo province. Indoor dwelling and outdoor temperatures were also analysed. Most participants perceived their dwellings to be too hot when it was hot outdoors. People relied on recommended heat health actions such as sitting outdoors in the shade or opening windows. While this agency is meaningful, resilience to climate change requires more than personal action. In light of the climate threats and climate-related disaster risks facing South Africa, an all-encompassing approach, including education campaigns, climate-proofed housing, access to basic services, and financial considerations that will help support resilient coping among South Africans, is urgently required.